Area under the Curve-Based Dosing of Vancomycin in Critically Ill Patients Using 6-Hour Urine Creatinine Clearance Measurement - Bita Shahrami; Farhad Najmeddin; Saeideh Ghaffari; Atabak Najafi; Mohammad Reza Rouini; Mojtaba Mojtahedzadeh (Critical Care Research and Practice)
Background. The area under the curve- (AUC-) guided vancomycin dosing is the best strategy for individualized therapy in critical illnesses. Since AUC can be calculated directly using drug clearance (CLvan), any parameter estimating CLvan will be able to achieve the goal of 24-hour AUC (AUC24 h). The present study was aimed to determine CLvan based on 6-hour urine creatinine clearance measurement in critically ill patients with normal renal function. Method. 23 adult critically ill patients with an estimated glomerular filtration rate (eGFR) ≥60 mL/min who received vancomycin infusion were enrolled in this pilot study. Vancomycin pharmacokinetic parameters were determined for each patient using serum concentration data and a one-compartment model provided by MONOLIX software using stochastic approximation expectation-maximization (SAEM) algorithm. Correlation of CLvan with the measured creatinine clearance in 6-hour urine collection (CL6 h) and estimated creatinine clearance by the Cockcroft–Gault formula (CLCG) was investigated. Results. Data analysis revealed that CL6 h had a stronger correlation with CLvan rather than CLCG (r = 0.823 vs. 0.594; p<0.001 vs. 0.003). The relationship between CLvan and CL6 h was utilized to develop the following equation for estimating CLvan: CLvan (mL/min) = ─137.4 + CL6 h (mL/min) + 2.5 IBW (kg) (R2 = 0.826, p<0.001). Regarding the described model, the following equation can be used to calculate the empirical dose of vancomycin for achieving the therapeutic goals in critically ill patients without renal impairment: total daily dose of vancomycin (mg) = (─137.4CL6-h (mL/min) + 2.5 IBW (kg)) × 0.06 AUC24 h (mg.hr/L). Conclusion. For AUC estimation, CLvan can be obtained by collecting urine in a 6-hour period with good approximation in critically ill patients with normal renal function.